Penegakan Hukum Terhadap Pelaku Pengedar Rokok Ilegal (Studi Kasus di KPPBC Tipe Madya Pabean A Pasuruan) - Imam Hanafi; Hariyo Sulistyantoro (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This phenomenon of illegal cigarette distribution can still be found in the Pasuruan area. The characteristics of illegal cigarettes include, among other things, excise stamps not being attached to cigarette packs, fake excise stamps being attached to cigarette packs and/or affixing excise stamps that do not correspond to their intended purpose. The Directorate General of Customs and Excise has the authority to take action and investigate illegal cigarette dealers in accordance with Law Number 39 of 2007 concerning Amendments to Law Number 11 of 1995 concerning Excise. The purpose of this research is to determine law enforcement against illegal cigarette dealers in the Pasuruan area by KPPBC Pasuruan. The research method used in this research is empirical juridical. Primary and secondary data were obtained through interviews with KPPBC Pasuruan enforcement and investigation section staff. The data analysis method is qualitative descriptive. The results of this research are that law enforcement carried out by KPPBC Pasuruan cannot be carried out optimally because in its implementation there are obstacles such as widespread distribution of cigarettes and a lack of officers. However, these various obstacles can be overcome with existing efforts.